2020
DOI: 10.3390/ani10071232
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecium Modulates the Gut Microbiota of Broilers and Enhances Phosphorus Absorption and Utilization

Abstract: Modern broiler chickens have ongoing bone health problems. Phosphorus (P) plays an important role in bone development and increased understanding of P metabolism should improve the skeletal health of broilers. Enterococcus faecium has been widely used as a probiotic in broiler production and is shown to improve skeletal health of rats, but its effect on the bones of broilers remains unclear. This study investigated the effect of E. faecium on P absorption and utilization in broilers and the associated changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…In addition, the salmonella-associated alteration of the gut microbiota could be a result of either pathogen-commensal microbiota interaction or host intestinal mucosal immune responses to the pathogen or even a combination of both ( 75 , 77 ). As previously reported, the supplementation of E. faecium significantly altered the gut microbiota composition of broilers and enriched the relative abundance of short-chain fatty acid-producing microbes ( 78 ). Also, E. faecium is a natural commensal bacteria of the poultry gastrointestinal tract and is commercially used as a probiotic in poultry diets ( 47 ), previous studies reported that numerous types of probiotic (e.g., Bacillus subtilis , Lactobacillus , and E. faecium ) supplementation can alter the community and structure of the gut microbiota and improve its diversity ( 11 , 79 81 ).…”
Section: Discussionsupporting
confidence: 64%
“…In addition, the salmonella-associated alteration of the gut microbiota could be a result of either pathogen-commensal microbiota interaction or host intestinal mucosal immune responses to the pathogen or even a combination of both ( 75 , 77 ). As previously reported, the supplementation of E. faecium significantly altered the gut microbiota composition of broilers and enriched the relative abundance of short-chain fatty acid-producing microbes ( 78 ). Also, E. faecium is a natural commensal bacteria of the poultry gastrointestinal tract and is commercially used as a probiotic in poultry diets ( 47 ), previous studies reported that numerous types of probiotic (e.g., Bacillus subtilis , Lactobacillus , and E. faecium ) supplementation can alter the community and structure of the gut microbiota and improve its diversity ( 11 , 79 81 ).…”
Section: Discussionsupporting
confidence: 64%
“…Recently, it has been demonstrated that the interactions between gut microbiota and phosphorus/vitamin D were crucial in bone development and mineralization. 36 , 37 The positive effects of Escherichia Faecium on phosphorus metabolism were associated with changes in Escherichia Shigella in broilers, which improved gut phosphorus absorption and bone-forming metabolic activities, and decreased phosphorus excretion. 36 However, bone minerals and apatite also serve as a dumping ground for trace elements and drugs, which seriously affects the bone health.…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 The positive effects of Escherichia Faecium on phosphorus metabolism were associated with changes in Escherichia Shigella in broilers, which improved gut phosphorus absorption and bone-forming metabolic activities, and decreased phosphorus excretion. 36 However, bone minerals and apatite also serve as a dumping ground for trace elements and drugs, which seriously affects the bone health. 38 Vitamin D3 supplementation decreased the relative abundance of Escherichia Shigella in the upper gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of IL-2 and INF-γ are downregulated ( 75 ). E. faecium supplementation upregulates the expression of intestinal-type IIb sodium-dependent phosphate cotransporter mRNA, increases the concentration of serum alkaline phosphatase, changes the gut microbiota populations, and increases the utilization of phosphorus ( 76 ). Bacillus subtilis BYS2 supplementation improves the production performance, immunity, and disease resistance; promotes innate immune response, increases the expression levels of interferon (IFN)-stimulated genes and β-defensins, and upregulates inflammatory cytokines ( 77 ).…”
Section: Antibiotic-free Management Strategies In Broilersmentioning
confidence: 99%